Examination of causes behind procrastination among Shahrekord University of Medical Sciences employees and proposing some strategies for their preventing: A study using the Van Wyk’s Model - Boldaji, Mohsen Khaksar; Shirvani, Alireza; Sharifi-Rad, Javad; Raeisi, Hamid; Rastar, Ali Akbar; Mirzaeian, Razieh (International Journal of Research in Medical Sciences, 2017)
Background: Competition among the organizations and enterprises plays a particularly important role in the gathering of the profits and acquisition of internal and external resources. Procrastination is one of the main barriers to efforts made towards increasing the productivity and efficiency in the organizations. Accordingly, the main goal of this research was to explore the reasons of procrastination among the employees based on Van Wyk’s model and present some strategies for preventing it. Methods: Descriptive-analytical in nature, this study was conducted on a sample of 200 employees selected from Shahrekord University of Medical Sciences using a self-designed checklist developed based on the informational components incorporated in the Van Wyk’s model. This model consists of 9 factors affecting the level of procrastination observed among the employees i.e. resistance, boredom, perfectionism, last-minute syndrome, lack of motivation for a task, fear of failure, skill deficit, rebelliousness and disorganization. The validity of the developed checklist was checked using its assessment by the expert professors and its reliability was measured with Cronbach's alpha. Both of them were confirmed (Cronbach's alpha of 90%). To analyze the data, T-test and variance analysis were used. Results: The results of the study showed that there was a statistically significant relationship between employee’s resistance, boredom, perfectionism and lack of motivation for task and procrastination (p=0.001); however, the association between fear of failure, rebelliousness and disorganization and procrastination was not statistically significant (p=0.871). Conclusions: The availability of high quality organizational capital will enhance the chance of organization’s success, survival and advancement. As a result, identifying the attributes of human resources and the factors influencing their efficiency so as to exploit the human capital more optimally and remove the reasons of procrastination is of high significance.